Mechanisms and diagnosis of myocardial ischemia in patients with intact coronary arteries - V.A. Skybchyk; Yu.P. Melen (Кардіохірургія та інтервенційна кардіологія)
This article describes pathogenetic mechanisms underlying the occurrence of myocardial ischemia and angina attacks in patients without ischemic non-obstructive coronary artery (INOCA) based on coronary angiography. Groups of patients who need additional invasive diagnosis with intracoronary administration of vasoactive agents (adenosine, acetylcholine) were identified. The diagnostic and technical features used during the invasive diagnostic procedure are presented in detail. The main indicators (coronary flow reserve, index of microvascular resistance, hyperemic microvascular resistance) are described. Particular attention is paid to the factors complicating interpretation of the results, as well as to the safety of this procedure. The information obtained during the invasive diagnostic procedure allows to determine the appropriate endotype of INOCA in order to make a correct diagnosis and prescribe effective drug treatment improving prognosis and quality of life.